2018
DOI: 10.5424/fs/2018272-11713
|View full text |Cite
|
Sign up to set email alerts
|

Estimating forest uniformity in Eucalyptus spp. and Pinus taeda L. stands using field measurements and structure from motion point clouds generated from unmanned aerial vehicle (UAV) data collection

Abstract: Aim of study: In this study we applied 3D point clouds generated by images obtained from an Unmanned Aerial Vehicle (UAV) to evaluate the uniformity of young forest stands.Area of study: Two commercial forest stands were selected, with two plots each. The forest species studied were Eucalyptus spp. and Pinus taeda L. and the trees had an age of 1.5 years.Material and methods: The individual trees were detected based on watershed segmentation and local maxima, using the spectral values stored in the point cloud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 1 publication
5
20
0
3
Order By: Relevance
“…The tendency of ALS and UAV-based DAP technologies to underestimate h may be the main reason for the underestimation of v with 1st approach. It should be also borne in mind that the ALS and UAV-based DAP, as a tree height estimation technique, tends to underestimate tree height (e.g., DAP [39,90,91], UAV-based DAP [47,74,76,92] and ALS [73,77,[93][94][95] point cloud data). However, our volume modelling results suggest that this bias may not influence in volume estimations using the 2nd approach, leaving open the question as to when and where specific models should be developed for correcting the bias at tree level depending on particular species or forest structure [77].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tendency of ALS and UAV-based DAP technologies to underestimate h may be the main reason for the underestimation of v with 1st approach. It should be also borne in mind that the ALS and UAV-based DAP, as a tree height estimation technique, tends to underestimate tree height (e.g., DAP [39,90,91], UAV-based DAP [47,74,76,92] and ALS [73,77,[93][94][95] point cloud data). However, our volume modelling results suggest that this bias may not influence in volume estimations using the 2nd approach, leaving open the question as to when and where specific models should be developed for correcting the bias at tree level depending on particular species or forest structure [77].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, ALS and SfM approaches to tree height estimation tend to underestimate tree height [73,74,76,77]. Recent studies [77] have presented a model that explains the observed bias using probability theory, developing methods for correcting several ALS metrics used for ABA prediction of stand structure.…”
Section: Introductionmentioning
confidence: 99%
“…Não diferente desse cenário, a silvicultura tem incorporado as evoluções da indústria 4.0, a fi m de otimizar a cadeia de produção fl orestal, trazer informações mais precisas, incrementar a produtividade e reduzir custos, desde a produção de mudas até ao consumidor fi nal, trazendo consigo diversos avanços, o que ocasionou a evolução para a fronteira da silvicultura 4.0. -GRANADOS et al, 2016a;LÓPEZ-GRANADOS et al, 2016b;DASH et al, 2017;RUZA et al, 2017;FEDUCK;MCDERMID;CASTILLA, 2018;HENTZ et al, 2018 Net, 2017;BONNEAU et al, 2017).…”
Section: Conclusãounclassified
“…Conforme resultados da revisão sistemática da literatura é possível observar que as ARP foram utilizadas em diversos estudos florestais voltados a individualização de árvores. Hentz et al (2018) utilizaram ARP na coleta de dados com sensor passivo com a finalidade de gerar nuvens de pontos tridimensionais, por correlação fotogramétrica em florestas de Eucalyptus spp. e Pinus taeda L. com idade de 1,5 anos, para posterior individualização baseada em segmentação de bacias hidrográficas e máximos locais atingindo um erro máximo de 6%.…”
Section: Artigo De Conferências 25unclassified